DBW443 (Karan Saanvi): A High Yielding, Biofortified Bread Wheat Variety for Irrigated TimelySown Conditions of Peninsular Zone, India: DBW443 (Karan Saanvi ) for Irrigated Timely-Sown Conditions of Peninsular Zone - Gupta, Vikas; Singh, Charan; Sharma, Amit Kumar; Tyagi, BS; Gupta, Arun; Kumar, Satish; Mishra, Chandra Nath; Kumar, Vishnu; Kamble, Umesh R; Sareen, Sindhu; Sheoran, Sonia; Bairwa, Rakesh K; et al. (Journal of Cereal Research, 2025)
The variety DBW443 is an indigenously developed biofortified wheat genotype from a cross of NW1014 /7th HLBSN 21. DBW443 was identified by the Varietal Identification committee during the in 63rd Annual Group Meeting of the All India Coordinated Research Project (AICRP) on Wheat and Barley held at ANDUA&T, Ayodhya from September 11-13, 2024. This variety was later released by the Central Sub-Committee on Crop Standards, Notification, and Release of Varieties, Ministry of Agriculture and Farmers Welfare, Government of India vide Gazette Notification No. S.O. 2128 (E) dated 13th May, 2025. The variety was released for irrigated timely sown conditions of Peninsular zone comprising states of Maharashtra and Karnataka.